2014
DOI: 10.1590/1677-3225v13n2a15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of finishing and polishing on surface roughness of composite resins after bleaching

Abstract: Aim: To evaluate the influence of finishing and polishing techniques on the surface roughness of two composite resins (CRs) subjected to bleaching procedure. Methods: Forty-eight CR specimens were divided into six groups (n=8). For G1 to G3, a microhybrid CR (Opallis; FGM) was used, and G4 to G6, received a nanohybrid CR (Brilliant NewLine; Coltène/Whaledent). All specimens were subjected to bleaching procedure with 35% hydrogen peroxide (two 45-min applications, with a 5-day interval). The surface roughness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…For PD group (felt disc + diamond paste), it is noted that this system considerably reduced the surface roughness left by the diamond tip, possibly because it has high hardness micronized abrasive diamond grains, wearing the particles that were exposed irregularly 15 . Just as in the current research, the findings of Martins Alves et al 15 and Bittencourt et al 23 also confirmed the influence of this polishing mechanism on the roughness of compound resins, visualizing a decrease in Ra values when used on rough surfaces. In contrast, Costa et al 2 suggest that the use of diamond paste in composite resins may be of value when used later on for instruments with aluminum oxide in the composition, in the case of this study, present in Sof-Lex and Enhance.…”
Section: Resultand Discussionsupporting
confidence: 88%
“…For PD group (felt disc + diamond paste), it is noted that this system considerably reduced the surface roughness left by the diamond tip, possibly because it has high hardness micronized abrasive diamond grains, wearing the particles that were exposed irregularly 15 . Just as in the current research, the findings of Martins Alves et al 15 and Bittencourt et al 23 also confirmed the influence of this polishing mechanism on the roughness of compound resins, visualizing a decrease in Ra values when used on rough surfaces. In contrast, Costa et al 2 suggest that the use of diamond paste in composite resins may be of value when used later on for instruments with aluminum oxide in the composition, in the case of this study, present in Sof-Lex and Enhance.…”
Section: Resultand Discussionsupporting
confidence: 88%
“…In contrast, IP contains nanosized and micrometric filler particles, and deep wear would expose nanosized and micrometric filler particles on the sub‐subsurface. In comparison with the felt discs used, Astropol rubber tips have increased hardness and deeper wear capability (Bittencourt et al, ). Thus, after SP, Astropol could expose nanosized filler particles in FZ and micrometric filler particles in IP, whereas the flexible felt discs did not create wear and exposed only the subsurface layer rich in nanosized filler particles in IP.…”
Section: Discussionmentioning
confidence: 99%
“…The bleaching agents can react differently with each phase or their interface. Bleaching treatments of restorative materials may affect surface gloss 5 , microhardness 6,8 , roughness 6,7,[9][10][11][12] , color [13][14][15][16] , and the amount of elutable components 17,18 . Surface polishing after bleaching may not restore the physical properties of the restorative material because subsurface layers up to 2.0 mm can be affected 8 .…”
Section: Introductionmentioning
confidence: 99%